Bangladesh Agricultural Research Council Marching Towards Digital Bangladesh - Das, Susmita (Journal of Agricultural Extension Management, 2021)
The Bangladesh Agricultural Research Council, in collaboration with other national agricultural research institutes, is working tirelessly to make Bangabandhu’s Sonar Bangla an upper-middle-income country by 2030 and a developed country by 2041 by achieving the Sustainable Development Goals. This paper presents the activities of the Bangladesh Agricultural Research Council, which are following the vision of Digital Bangladesh in opening up all the data and information related to agricultural research outputs for all the farmers and the stakeholders of the National Agricultural Research System of Bangladesh